2013
DOI: 10.1200/jco.2013.31.15_suppl.6036
|View full text |Cite
|
Sign up to set email alerts
|

CAPRA: Safety, efficacy, and translational biomarkers of weekly everolimus, carboplatin, and paclitaxel as induction therapy for locally advanced head and neck squamous cell carcinoma (HNSCC).

Abstract: 6036 Background: ThePI3K/mTOR pathway is activated in >50% of HNSCC with preclinical synergism between everolimus and carboplatin/paclitaxel. Methods: Patients (pts) with untreated locally advanced HNSCC with ECOG PS<2 received 9 consecutive weekly (w) cycles (cy) of CAPRA combining everolimus (30 mg/w at dose-level 1 then 50 mg/w at dose-level 2) with carboplatin (AUC2) and paclitaxel (60 mg/m2) followed by chemoradiotherapy. Endpoints were safety (CTCv3.0), antitumor activity (RECIST1.1), pharmacodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The most impressive response, however, has come from the ongoing phase I‐II trials of everolimus in combination with carboplatin and paclitaxel as induction therapy in patients with unresectable locally advanced HNSCC. Recently presented results showed a 2.6% complete response, 76.3% partial response, as well as 21% stable disease in the 38 evaluable patients (Raymond et al , ). Everolimus continues to be investigated alone and in combinations in patients with HNSCC in five additional phase I‐II trials (Table ).…”
Section: Pi3k/akt/mtor Inhibitors In Clinical Studiesmentioning
confidence: 93%
“…The most impressive response, however, has come from the ongoing phase I‐II trials of everolimus in combination with carboplatin and paclitaxel as induction therapy in patients with unresectable locally advanced HNSCC. Recently presented results showed a 2.6% complete response, 76.3% partial response, as well as 21% stable disease in the 38 evaluable patients (Raymond et al , ). Everolimus continues to be investigated alone and in combinations in patients with HNSCC in five additional phase I‐II trials (Table ).…”
Section: Pi3k/akt/mtor Inhibitors In Clinical Studiesmentioning
confidence: 93%
“…The number of clinical trials determined to evaluate the efficacy of the inhibitors of AKT, mTOR, or the AKT/mTOR pathway in OC patients is very few. However, several clinical trials have been reported with details of such investigation in HNSCC patients (Table 3) [191][192][193][194][195][196][197][198][199][200][201][202][203][204][205]. Some of these trials have been completed or terminated, while some are still ongoing.…”
Section: Inhibitors In Clinical Studiesmentioning
confidence: 99%
“…Therefore, several clinical trials were conducted in HNC patients where everolimus was administered in combination with other drugs such as cetuximab, erlotinib, carboplatin and cetuximab, carboplatin and paclitaxel, cisplatin and docetaxel, cisplatin or carboplatin and cetuximab and cisplatin and radiotherapy. Most of these studies have been completed [193][194][195][196] (NCT01637194, NCT00942734, NCT01283334, NCT01333085, NCT00935961) while a few combinations have been discontinued due to severe side effects (NCT01009346, NCT01057277). However, the regime (everolimus, cisplatin and radiotherapy) was well tolerated in HNC patients with promising efficacy (NCT00858663) [197].…”
Section: Everolimusmentioning
confidence: 99%
“…Everolimus, an mTORC1 inhibitor, is undergoing a trial as part of a Phase I/II study investigating induction chemotherapy with weekly everolimus plus carboplatin and paclitaxel in locally unresectable advanced HNSCC. The treatment is well tolerated with an overall response rate of 79% (52). Another Phase I and pharmacokinetic study of everolimus in combination with cetuximab and carboplatin for recurrent or metastatic HNSCC showed an encouraging response rate, with 61.5% and 8.15 months progression-free survival, which suggested possible clinical efficacy in a select group of patients with cSCC (49).…”
Section: Discussionmentioning
confidence: 97%